Detecção molecular e sorológica de Ehrlichia spp. em felinos domésticos da região metropolitana de Cuiabá, Brasil - Braga, Ísis Assis (2013)
Ehrlichiosis is a disease of worldwide distribution, caused by the rickettsial agent Ehrlichia spp.. The occurrence in dogs is considered endemic in several regions of Brazil. However, this information in cats is unknown and few studies have been performed to date in Brazil. In order to detect the presence of Ehrlichia spp. in cats from the metropolitan area of Cuiabá, Mato Grosso state, blood and serum samples were collected from a regional population of 212 individuals and tested by Immunofluorescence Assay (IFA) and the Polymerase Chain Reaction (PCR) designed to amplify a 409 bp fragment of the dsb gene. Eighty-eight (41.5%) animals were seropositive by IFAT and 20 (9.4%) were PCR positive. Partial sequences of DNA obtained from PCR products were identical to the GenBank E. canis sequences. Twelve cats were positive in both molecular and serological tests. Association tests, based on clinical and laboratory findings of a partial evaluated population, showed that seropositive cats presenting pale mucous membranes and lower counts of erythrocytes as associated variables (p ≤ 0.05). Tick infestation was not observed at blood collection. This study complements the demand for more information on this species, reporting the presence and the first molecular and serological detection of E. canis infection in cats from the metropolitan area of Cuiabá, Midwest region in Brazil.